Peran Pendidikan Dalam Mendukung Sustainable Develompent Goals (SDGs) - Fitriyah, Ayda; Nugraheni, Nursiwi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Currently, the world is experiencing complex and dynamic developments, with its problems. People around us are often faced with social and economic challenges such as conflict, social inequality and poverty. Education for sustainable development is expected to produce a generation that has a sustainable mindset. Currently, Indonesia is trying to improve the quality of its education through implementing the